The practice of industrial policy - Lessons for Africa. Case studies of decentralized co-ordination in China - Hinh T. Dinh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper draws on both successful and failing cases of industrialization in China to analyse the role of local governments in fostering the growth of light manufacturing. The broad spectrum of support types and the intimate knowledge of enterprise conditions by these local governments make their support effective particularly for the business expansion and cluster development. Local government policies toward enterprises are dynamic and tailor to the needs that arise at the various stages of the life cycles of firms, from start-up to growth and maturity. Government assistance has not always involved spending money. The successful outcome is a result of 'backing the winner' approach.
Keywords: H73; L52; L60; O14; 330; Africa; China; industrial policy; industrialization; decentralized co-ordination